Further evidence on idiosyncratic risk and REIT pricing: a cross-country analysis. Issue 1 (3rd May 2016) - Mi, Lin; Benson, Karen; Faff, Robert
Abstract : Purpose: The purpose of this study is to provide new cross-country evidence on the relation between real estate investment trust (REIT) returns and idiosyncratic risk for samples of listed and unlisted REITs in the US and Australia. Design/methodology/approach: Five alternative models with exponential GARCH enhancements were employed, in a Fama-MacBeth (1973) setup. The authors assess the statistical significance of the idiosyncratic risk variable and interpret the outcomes. Findings: The results show that listed REITs in the US and Australia demonstrate a positive idiosyncratic risk-return linkage over the long period of January 1980-November 2013 and April 1994-December 2012, respectively. A further examination by sub-period reveals that this positive relation is only evident in the new REIT era (January 1993-September 2001), absent in the vintage era (before December 1992) and maturity era (November 2001-August 2008). The unlisted REITs in both countries show no relation with idiosyncratic risk. Further, the global financial crisis has no effect on the relation between idiosyncratic risk and REIT returns. Originality/value: A key motivation of this paper stems from the mixed findings documented in the literature. Also very little research has been done on the idiosyncratic risk-REIT returns linkage in the Australian context. This study offers unique insights from comparisons: Australia vs the US; and listed vs unlisted REITs.